Isaac Transfigured: The Aqedah as Mashal in Matthean Midrash - Smith, David Andrew (The catholic biblical quarterly, 2022)
This article combines intertextual and comparative midrashic approaches to argue that the story of Jesus's transfiguration in the Gospel of Matthew, understood in light of a set of concerted intertextual connections among Matthew, the story of Isaac's Aqedah in Genesis 22, and a number of parallel Jewish interpretive traditions, should be read as a proleptic passion narrative. By assessing the intertextual relationship between Matt 17:1-9 and Gen 22:1-19 LXX more thoroughly than has been done previously (particularly as regards the Greek form of the Aqedah) and by giving sustained attention to points of contact between Matthew's use of the Aqedah as a narrative explicating the life of Jesus and early Jewish midrashim interpreting the Aqedah in light of the history of Israel, I argue that the ancient story of Isaac functions according to the midrashic technique of the mashal.